The Effect Of Interval Training On Liver Enzyme Activity In Fitness Practitioners - Almajed, Amjad Abdul Hamid (Indonesian Journal Publisher, 2024)
The study aimed to develop targeted specialized exercises when practicing fitness activity and then know the activity (GPT and GOT) as variables reflecting the image of cell degradation or preservation as a result of adaptation to the level of functional devices, so the experimental method was chosen by the method of one sample as a way to solve the issue. The researcher used a deliberate sample of (10) practices and used training with a training intensity of (50-80%) for two months at 3 units per week, the time of each training unit (60d), then the researcher conducted post-tests and used statistical methods for treatment. The results were presented in tables and the most important conclusions were that specialized training contributes to the stability of GPT and GOT enzymes and is not affected to the degree of high altitude.